Analisis Perawatan Mesin Bubut CD6250C Dengan Metode Reliability Centered Maintenance (RCM) di PT. XYZ - Baharudin, Habib; Rizaldi, Dedi; El Atros, Mochammad Rajib (Jurnal Teknik Mesin, 2025)
PT XYZ is one of the industries engaged in the manufacturer of agricultural, plantation, industrial equipment / machinery that can make / engineer tools / machines. Conventional lathe is one of the production machines in PT XYZ. Lathe machines are often damaged so they require maintenance. This study aims to provide maintenance proposals for conventional lathe machines through the application of the RCM approach in order to get a more effective and efficient maintenance strategy, the application of RCM starts from identifying system functions and malfunctions, Intermediate Decision Tree (IDT) analysis and Logic Tree Analysis (LTA), Failure Mode and Effect Analisys (FMEA) analysis, Mean Time Between Failure (MTBF) and Mean Time To Repair (MTTR) analysis and selection of maintenance proposals. From the results of the RCM analysis of conventional lathe machines, it is obtained that the components that have the largest Risk Priority Number (RPN) are Lathe Chisels 54 RPN, Chuck / Chamfer 30 RPN, V-Belt & Pulley 20 RPN. The results of the proposed maintenance for lathe machines are Preventive Maintenance, component maintenance is carried out before experiencing damage such as chuck before 1112.5 hours of use, Lathe Chisel before 185.08 hours of use, V-Belt + Pulley must be repaired before 2226 hours according to MTBF calculations.